Odpowiedź :
Odpowiedź:
-4w-w+2w-15 = -3w - 15
3x+1+2x = 5x + 1
5-4x+2 = -4x + 7
0,4x-0,4+x = 1,4x - 0,4
6/8x+4+2/8x = x + 4
3a-8a+2a-4 = -3a - 4
4b-4+4b+1 = 8b - 3
z-4z-2+2z = -z - 2
3/5b-2b-2/5-b = 2 2/5b - 2/5
3 1/2-x+0,3x-2 = -0,7x + 1 1/2
-x+7-4x+3 = -5x + 10
x-3x+2-0,2x-1/7 = -2,2x + 1 6/7
2x-4-3x-2 = -x - 6
-5x+4-7x-9 = -12x - 5
2x+4x+3x-2 = 9x - 2
Odpowiedź:
- 4w -w +2w -15= -3w -15
3x+1 + 2x= 5x+1
5-4x+2= 7-4x
0,4x - 0,4 +x= 1,4x -0,4
6/8x +4 +2/8x= x+4
3a-8a +2a-4= -3a -4
4b- 4 +4b+1=8b -3
z-4z -2+2z= - z -2
3/5 b -2b - 2/5-b= - 2 i 2/5b - 2/5
3 i 1/2 - x +0,3x -2= - 0,7x+1 i 1/2
-x +7 -4x +3= -5x +10
x- 3x +2 - 0,2x -1/7= -2,2x + 1 i 6/7
2x-4 -3x -2= -x -6
-5x +4-7x -9= - 12x -5
2x+4x +3x -2= 9x-2
Szczegółowe wyjaśnienie: